Masculinities and third gender the origins and nature of an institutionalized gender otherness in the ancient Near East - Peled, Ilan 1969-; Ugarit-Verlag Buch- und Medienhandel GmbH (Münster Ugarit-Verlag, 2016)
The aim of this book is to track a distinct human phenomenon in the history of the ancient Near East: persons who were born males, but under various social and historical circumstances their masculine identity was considered to be ambiguous. On the basis of this, these persons can be classified as belonging to a third gender. They bore specific titles, and were engaged in cult or palace administration. The contexts of their documentation occasionally depict them as possessing or exhibiting traits that were uncharacteristic of the standard social expectations of men in Mesopotamia. 0The present research demonstrated that this human phenomenon of a third gender in the ancient Near East involved mainly the matter of social definitions. Social identity is defined by its limitations: where it begins and ends, and what exists beyond it. The strange, the extreme and the bizarre signify what common, hegemonic, people are not, and therefore mark who common, hegemonic, people actually are. These boundaries are constructed by using social mechanisms of norms and prohibitions. In this sense, the third gender figures were socially constructed, and served social needs of defining norms of conformity
Introduction. Aims, scope, methodology and structure of the book ; Third gender: ambiguous masculinity and social conformity ; Male third gender figures in the ancient Near East: history of research ; The formation of masculinity (and femininity): theoretical perspectives ; The features of hegemonic masculinity in the ancient Near East -- Mesopotamian narrative and hymnic texts. Introduction ; Inanna/Istar's descent to the netherworld ; The fashioning of the gala ; Inanna and Ebih ; Inanna and Enki ; Lady of the largest heart ; This city, which has been looted ; The epic of Erra ; A myth of Dumuzi ; Enki and Ninmah ; Gilgames and Aga ; The curse of Akkad ; The lament for Eridu ; The debate between grain and sheep -- gala, kalu and kulu'u. Introduction ; gala/kalu and gala-mah/kalamahu ; General introduction ; gala/kalu and gala-mah/kalamahu: chronological survey ; gala/kalu: origins of the terms and possible etymologies ; The question of the Emesal-dialect ; gala/kalu in Mesopotamian narrative texts ; Non-textual sources: gala/kalu in Mesopotamian art ; Gender ambiguity of the gala/kalu ; kulu'u ;General introduction ; The evidence concerning kulu'u -- assinnu and kurgarru in lexical lists ; assinnu and kurgarru in administrative and historical texts ; assinnu and prophecy in Mari and the ancient Near East ; assinnu and kurgarru in Cultic texts ; assommi and kurgarru in narrative texts ; assinnu and kurgarru in omen, ritual and incantation texts -- lu-sag / sa resi and castration in the ancient Near East ; Introduction ; lu-sag / sa resi: brief chronological survey of the titles ; lu-sag / sa resi: the evidence of castration ; Castration from theoretical and clinical perspectives -- Less known third gender figures. Introduction ; girsequ ; tiru/tiru ; SAG-UR-SAG ; pi-li-pi-li/pilpilu ; sinnisanu ; nas pilaqqi ; paru -- Summary and conclusions. Summaries and conclusion of individual chapters ; Internal division to sub-categories within the third gender ; Masculinities and third gender in the wider context: castration, hyomosexuality and Cultic performance ; Third gender and hegemonic and subordinate masculinities ; In conclusion: why third gender?
"This book is a heavily revised version of my PhD dissertation" (Vorwort)
Keywords: Extinct languages -- Sex differences -- Middle East; Language and sex -- Middle East; Sex -- Middle East -- History; Hochschulschrift